Comparison of statistical properties of coolant temperature and neutron flux in a reactor PWR-1000 - Skorbun, A.D.; Stadnyk, S.M.; Kotelenets, V.G.; Arvaninov, O.L.; Drobetskii, A.V. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Using wavelet analysis an existence of regularities in “noise” signals from neutron flux detectors and temperature ones of a design in-pile control system of PWR-1000 reactor was investigated. For the purpose to check the possibility to estimate coolant parameters through neutron flux parameters and vice versa, a comparative analysis of statistical characteristics for parallel long regular sets of measurements of coolant temperature and a neutron flux was carried out. It were analyzed neutron signals from three measurement canals with ionization chambers, and from temperature sensors for coolant of the cool and hot branches of the first contour. In both variables a rich spectrum of various long time (tens of minutes and hours) periodicities has been revealed. Some of them are found both in temperatures and in the neutrons flux. It was however revealed also periodicities, which in neutrons and in a coolant do not correlate between themselves. The differences between the pictures of wavelet transform of temperatures of hot and cold branches of the first contour have been shown. In the temperature of hot branch additional more high frequency vibrations, which can be ascribed to development of turbulence, are arisen. The conclusion was drawn, that fluctuations of signals, that have been analyzed, are not random noise, but are the data carrier about neutron subsystem of a reactor. It is suggested to carry out the analysis of fluctuations of signals of a design in-pile control system for early detection of a reactor operating conditions. Із використанням вейвлет-аналізу досліджено наявність закономірностей у «шумових» сигналах детекторів нейтронного потоку і температури теплоносія штатної системи внутрішньореакторного контролю реактора ВВЕР-1000. Виконано порівняльний аналіз довгих рядів вимірювань температури теплоносія і щільності потоку нейтронів. В обох параметрах виявлено багатий спектр різноманітних періодичностей. Деякі з них знайдено як у даних температури, так і потоку нейтронів. Проте в динаміці потоку нейтронів і температури виявлено також періодичності, які не корелюють між собою. Показано відмінності між картинами вейвлет-перетворення температур гарячої і холодної ниток: у температурі гарячої нитки виникають додаткові більш високочастотні коливання, які можна приписати розвитку турбулентності. Зроблено висновок, що проаналізовані флуктуації сигналів не є випадковим шумом, а є носіями інформації про стан нейтронної підсистеми реактора. Пропонується виконувати аналіз флуктуацій сигналів штатної системи контролю для діагностики режимів роботи реактора. С использованием вейвлет-анализа изучено существование закономерностей в «шумовых» сигналах детекторов потока нейтронов и температуры теплоносителя штатной системы внутриреакторного контроля реактора ВВЭР-1000. Выполнен сравнительный анализ длинных рядов измерений температуры теплоносителя и плотности потока нейтронов. В обоих параметрах обнаружен богатый спектр разнообразных периодичностей. Некоторые из них найдены как в температурных данных, так и данных потока нейтронов. Однако в динамике потока нейтронов и температуры обнаружены также периодичности, которые не коррелируют между собой. Показаны отличия между картинами вейвлет-преобразования температур горячей и холодной ниток: в температуре горячей нитки возникают дополнительные более высокочастотные колебания, которые можно приписать развитию турбулентности. Сделан вывод, что проанализированные флуктуации сигналов не являются случайным шумом, а являются носителями информации о состоянии нейтронной подсистемы реактора. Предлагается выполнять анализ флуктуаций сигналов штатной системы внутриреакторного контроля для диагностики режимов работы реактора.